HIV-1 Persistence in Children during Suppressive ART - Mary Grace Katusiime; Gert U. Van Zyl; Mark F. Cotton; Mary F. Kearney (Viruses, 2021)
There is a growing number of perinatally HIV-1-infected children worldwide who must maintain life-long ART. In early life, HIV-1 infection is established in an immunologically inexperienced environment in which maternal ART and immune dynamics during pregnancy play a role in reservoir establishment. Children that initiated early antiretroviral therapy (ART) and maintained long-term suppression of viremia have smaller and less diverse HIV reservoirs than adults, although their proviral landscape during ART is reported to be similar to that of adults. The ability of these early infected cells to persist long-term through clonal expansion poses a major barrier to finding a cure. Furthermore, the effects of life-long HIV persistence and ART are yet to be understood, but growing evidence suggests that these individuals are at an increased risk for developing non-AIDS-related comorbidities, which underscores the need for an HIV cure.